Political participation in a changing world conceptual and empirical challenges in the study of citizen engagement - Theocharis, Yannis; Deth, Jan W. van (Routledge, 2018)
"In the last decades, political participation expanded continuously. This expansion includes activities as diverse as voting, tweeting, signing petitions, changing your social media profile, demonstrating, boycotting products, joining flash mobs, attending meetings, throwing seedbombs, and donating money. But if political participation is so diverse, how do we recognize participation when we see it? Despite the growing interest in new forms of citizen engagement in politics, there is virtually no systematic research investigating what these new and emerging forms of engagement look like, how prevalent they are in various societies, and how they fit within the broader structure of well-known participatory acts conceptually and empirically. The rapid spread of internet-based activities especially underlines the urgency to deal with such challenges. In this book, Yannis Theocharis and Jan W. van Deth put forward a systematic and unified approach to explore political participation and offer new conceptual and empirical tools with which to study it. Political Participation in a Changing World will assist both scholars and students of political behavior to systematically study new forms of political participation without losing track of more conventional political activities."--Provided by publisher.